Morphology-controlled fabrication of NiCo2S4 nanostructures decorating carbon nanofibers as low-cost counter electrode for efficient dye-sensitized solar cells. (20th January 2021) - Qiu, Ju; He, Dayong; Wang, Hao; Li, Wenyan; Sun, Bolun; Ma, Yuying; Lu, Xiaofeng; Wang, Ce
Abstract: The development of highly efficient, earth-abundant and low-cost counter electrode materials is of significant importance and challenge for practical application in dye-sensitized solar cells. In this work, morphology-controlled NiCo2 S4 nanoparticles (NPs) and nanorods (NRs) decorating carbon nanofibers (CNFs) have been prepared via an electrospinning and hydrothermal or solvothermal strategy, which are further utilized as counter electrodes (CEs) in dye-sensitized solar cells (DSSCs). Benefitting from the rich nickel and cobalt ions redox chemistry and more exposed catalytically active sites from NiCo2 S4 NRs grown vertically on the surface of CNFs as well as faster electron transporting capability providing by the highly conductive CNFs, the DSSC device based on NiCo2 S4 NRs/CNFs CE yields an excellent power conversion efficiency of 9.47%, which is higher than that of the devices with NiCo2 S4 NPs/CNFs (8.63%), Pt (8.18%) and CNFs (6.06%) as CEs under AM 1.5 G irradiation. Furthermore, the NiCo2 S4 NRs/CNFs CE shows an excellent electrochemical stability in an iodine-based electrolyte. This study highlights a controllable and versatile route to rational design efficient counter electrode catalysts for high-performance CEs application.